Development of Creative Puppet Mediaito Increase Students’IInterest in Learning Learning History in Class XI at Al-Fityah Highschol Pekanbaru - Nadira Nurul Atika; Bunari Bunari; Yuliantoro Yuliantoro (JURNAL PENDIDIKAN IPS, 2025)
Education is an effort in the process of becoming an active individual in developing the potential that exists within him. Learning media is one component of the teaching and learning process which has an important role in supporting the success of the teaching and learning process in the classroom. However, with modern developments, wayang can be used as an educational and effective medium in learning with different packaging and attracting students' learning interest. This research aims to develop Wayang Kreasi media regarding Colonialism and Indonesian National Resistance, especially the Diponegoro War material. This type of research is development research with the ADDIE development model, namely analysis, design, development, implementation and evaluation. The results of the validation of Wayang Kreasi media experts from material experts with a score of 47 with a percentage of 94%, from media experts with a score of 45 with a percentage of 90%, from the Teacher Response Questionnaire with a score of 46 with a percentage of 83.63%, the results of the small group learning interest questionnaire with a score of 360 of the 6 students who have been selected with a percentage of 92.30% and a media assessment of 86.15%. The results of the study interest questionnaire for a large group of 23 students found a score of 1311 with a percentage of 87.69% and a media assessment of 83.07% in the "Very Appropriate" category. It can be said that the Wayang Kreasi learning media can be used as a means to increase students' interest in learning.